If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -7x + -2 = -22 + 3x + -13 Reorder the terms: 7 + -2 + -7x = -22 + 3x + -13 Combine like terms: 7 + -2 = 5 5 + -7x = -22 + 3x + -13 Reorder the terms: 5 + -7x = -22 + -13 + 3x Combine like terms: -22 + -13 = -35 5 + -7x = -35 + 3x Solving 5 + -7x = -35 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -7x + -3x = -35 + 3x + -3x Combine like terms: -7x + -3x = -10x 5 + -10x = -35 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -10x = -35 + 0 5 + -10x = -35 Add '-5' to each side of the equation. 5 + -5 + -10x = -35 + -5 Combine like terms: 5 + -5 = 0 0 + -10x = -35 + -5 -10x = -35 + -5 Combine like terms: -35 + -5 = -40 -10x = -40 Divide each side by '-10'. x = 4 Simplifying x = 4
| 7/5=10.5b | | 10b^2-26b+12=0 | | X/3-5=-4 | | 8-y=15 | | 5x=-5y+65 | | 7-9x-2=-46+7x-13 | | X^2+2x+.4=.9x^2+x | | X=-5y+25 | | (5x+6)(5x-5)= | | -9x-5=9-2x | | -16/3/2/3 | | 2m/n-5m/3n | | 3y-2=6-y | | .5(6x+4)=4x-9 | | -51/3x/2/3 | | 15(b+6)-9b= | | 3x^4+19x^3+6x^2=0 | | 2p^2+21p+40=0 | | -56=a^2+18a | | 3/4(4x8-8)=-10 | | -6=2a-3 | | 7-8x-3=-65+6x-15 | | 4d+5d=54 | | 11/3x22/5 | | (r^10-1)/(r^30-1) | | x/9+15=19 | | .5x+6-2x+.5=7/2 | | 2k^2+11k-40=0 | | 9+5[a-4(a-5)]= | | 2x+14.4= | | (4x+12)-6=26 | | 26+(-46)+(-26)= |